2009
DOI: 10.1016/j.chembiol.2009.09.013
|View full text |Cite
|
Sign up to set email alerts
|

β-Glycosyl Azides as Substrates for α-Glycosynthases: Preparation of Efficient α-L-Fucosynthases

Abstract: Fucose-containing oligosaccharides play a central role in physio-pathological events, and fucosylated oligosaccharides have interesting potential applications in biomedicine. No methods for the large-scale production of oligosaccharides are currently available, but the chemo-enzymatic approach is very promising. Glycosynthases, mutated glycosidases that synthesize oligosaccharides in high yields, have been demonstrated to be an interesting alternative. However, examples of glycosynthases available so far are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
91
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 49 publications
2
91
1
Order By: Relevance
“…8D). The β-glucosyl moiety at subsite +1 was tightly surrounded by 5 these amino-acid residues, and the carboxy group of Glu174 established a hydrogen bond with 6 the O2 atom (Fig. 8C, D).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…8D). The β-glucosyl moiety at subsite +1 was tightly surrounded by 5 these amino-acid residues, and the carboxy group of Glu174 established a hydrogen bond with 6 the O2 atom (Fig. 8C, D).…”
mentioning
confidence: 99%
“…4 A single trisaccharide species (ESI-MS: m/z 527.16 for C18H32O16 + Na + ) was produced 5 when lactose was used as the acceptor molecule. The NMR spectra indicated that the trisaccharide 6 was β-lactosyl α-D-galactopyranoside [α-D-Galp-(1↔1)-β-D-Glcp-(4←1)β-D-Galp; Gal-Lac], 7 which respective occupancies of β-glucosyl and β-galactosyl moieties at subsites +1 and +2 8 formed. The α-(1↔1)-β linkage was determined by the HMBC-correlation between H-1 (J = 8.2 9 Hz) of the glucose residue and C-1 of the galactose residue, and that between H-1 (J = 3.8 Hz) of 10 the galactose residue and C-1 of the glucose residue (Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations